Tourism policy in Algeria: : qualifications, actors, areas of expansion and tourist sites in the wilaya of Constantine. - Boufenara, Fatima; Boukerzaza, Housni (Journal of Human Sciences, 2020)
In recent years, Algeria had an effective and ambitious policy to resurrect the tourism sector and to develop investment by strengthening the elements of tourism attraction in a country with all assets and qualifications. To this end, Algeria has taken various measures to enhance its tourism capacity by creating touristic expansion zones as part of a tourism development plan that clarifies the consultative role of national, local and public stakeholders. This is to enable them to express their opinions and concerns and their proposals before this plan became a mandatory tool to apply. The province of Constantine has various tourism possibilities, which will be valorized through the regulation of these areas intended for expansion, in order to provide a real estate reserve for investment and diversification of tourism product across the territory of the state